Colchicine-Resistant Familial Mediterranean Fever With Depressive State Successfully Treated With Escitalopram - Toshida, Masamitsu (Cureus, 2021)
Familial Mediterranean fever (FMF) is a hereditary autoinflammatory disease associated with the Mediterranean fever (MEFV) gene and is mainly characterized by periodic fever and serositis. Colchicine has been used to prevent FMF episodes and reduce the frequency of attacks. We report the case of a 64-year-old man who presented with depressive symptoms and was resistant to colchicine treatment. Adding escitalopram to the ongoing colchicine regimen dramatically improved his fever, abdominal pain, and depressive symptoms. The change in cytokines, ABCB1 effects, and increased serotonin were related to these mechanisms. This case suggested that adding escitalopram to colchicine is a viable treatment option for colchicine-resistant FMF.